Halal gastronomy: handling food products' quality in the local tourism market - Saffinee, Siti Syahirah; Jamaludin, Mohammad Aizat (Penerbit UnisZA, 2024)
The growing demand for halal products, aligned with consumers' moral and religious standards, is driving the rapid expansion of the halal business, particularly in the travel and hospitality sectors. This study aims to evaluate the quality of halal products and their influence on the local tourism industry. Specifically, it investigates the key quality components of halal gastronomy and addresses stakeholders' challenges in maintaining and improving these standards to meet the needs of Muslim tourists. Using a qualitative descriptive analysis based on existing literature and data, the study provides an in-depth exploration of the factors influencing halal cuisine quality, including hygiene, authenticity, and compliance with Islamic dietary principles. The analysis highlights how the quality of halal food impacts Muslim tourists' experiences and the local tourism market's appeal. The findings reveal significant challenges in ensuring high-quality halal products, such as maintaining consistency across the supply chain and adhering to strict halal standards. Strategies for overcoming these challenges, such as improved quality control, certification processes, and stakeholder collaboration, are discussed. This study offers practical recommendations for stakeholders in the local tourism sector to enhance the quality of halal gastronomy, thereby improving tourist satisfaction and destination competitiveness. It contributes to the existing literature by filling a gap in the understanding of halal product quality and its implications for halal tourism. This research provides valuable insights for businesses and policymakers aiming to attract and accommodate Muslim travelers by maintaining high halal food standards.